THE EFFECTIVENESS OF BRAINSTORMING METHOD AND AUDIO-VISUAL MEDIA ON THE LEARNING OUTCOMES OF ELEMENTARY SCHOOL IPS STUDENTS - Anggara Dwinata; Emy Yunita Rahma Pratiwi; Muhammad Nuruddin (Universitas Majalengka, 2023)
This research is motivated by the results of researchers' observations that students in understanding Social Sciences (IPS) learning materials are less able to support achieving maximum learning outcomes. So an exciting treatment is needed using the Brainstorming method and audio-visual media to give a significant impact effectively. The research objective was to determine the effectiveness of the treatment of student learning outcomes in Social Science learning through the Brainstorming method supported by Audio Visual media for fourth-grade students at SDN Grogol 1, Kediri Regency. The research method used is quantitative, with the True-Experimental-Design research technique using two classes, namely the control and experimental classes. The research sample was fourth-grade students at SDN Grogol 1, Kediri Regency, for the 2021/2022 academic year, totaling 40 students. Data collection techniques in research are tests. The analysis technique used with the t-test (Independent Sample t-test) is used to test the effectiveness of using the Brainstorming method, which is supported by Audio Visual media in learning Social Sciences (IPS). The results showed that the probability (Sig. 2-tailed) = 0.002 <0.05 (significance level) and a t-count of 3.206 was more significant than a t-table of 2.009. The conclusions in the study provide evidence that the effectiveness of the Brainstorming method supported by Audio Visual media can improve learning outcomes in Social Sciences (IPS) in class IV Elementary School students. Penelitian ini dilatarbelakangi melalui hasil pengamatan peneliti bahwa siswa dalam memahami materi pembelajaran Ilmu Pengetahuan Sosial (IPS) kurang mampu mendukung tercapainya hasil belajar yang maksimal, sehingga dibutuhkan perlakuan yang menarik dengan menggunakan metode Brainstorming dan media audio visual sebagai bentuk efektivitas dalam memberikan dampak secara signifikan. Tujuan penelitian adalah untuk mengetahui efektivitas perlakuan terhadap hasil belajar siswa pada pembelajaran Ilmu Pengetahuan Sosial melalui metode Brainstorming yang didukung media Audio Visual siswa kelas IV SDN Grogol 1 Kabupaten Kediri. Metode penelitian yang digunakan adalah metode kuantitatif dengan teknik penelitian True-Experimental-Design dengan menggunakan dua kelas yaitu kelas kontrol dan kelas eksperimen. Sampel penelitian adalah siswa kelas IV SDN Grogol 1 Kabupaten Kediri tahun ajaran 2021/2022 yang berjumlah 40 siswa. Teknik pengumpulan data dalam penelitian adalah tes. Teknik analisis yang digunakan dengan uji-t (Independent Sample t-test) digunakan untuk menguji tingkat efektivitas penggunaan metode Brainstorming yang di dukung media Audio Visual dalam pembelajaran Ilmu Pengetahuan Sosial (IPS). Hasil penelitian menunjukkan besarnya probabilitas (Sig. 2-tailed) = 0,002 < 0,05 (taraf signifikasi) dan diperoleh t-hitung sebesar 3,206 lebih besar dibandingkan t-tabel sebesar 2,009. Simpulan dalam penelitian memberikan bukti bahwa efektivitas metode Brainstorming yang didukung media Audio Visual dapat meningkatkan hasil belajar Ilmu Pengetahuan Sosial (IPS) pada siswa kelas IV Sekolah Dasar.